PERAN RELASI SAUDARA KANDUNG DALAM PERKEMBANGAN EMOSIONAL ANAK - Zahra Cahya Permata Gunawan (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2026)
Children's emotional development is an important aspect in the formation of psychological well-being and emotional regulation abilities. In addition to the role of parents, sibling relationships also contribute to providing emotional support for children, but their role has received relatively little attention in empirical studies. This study aims to explore and understand the role of sibling relationships in children's emotional development based on the experiences of the children as research subjects. The study uses a qualitative approach with a descriptive qualitative design. The research subjects were children who have siblings, selected through purposive sampling techniques. Data were collected through in-depth interviews, non-participant observation, and documentation. Data analysis was conducted qualitatively through data reduction, data presentation, and conclusion drawing, while the validity of the data was ensured through source and technique triangulation. The results of the study indicate that sibling relationships play a role in providing emotional support through closeness in relationships, cooperation in daily activities, and the ability to show attention and support when facing problems. Conflicts between siblings were also found in daily interactions; however, these conflicts were generally minor and could be resolved through communication or parental guidance. In addition, interactions between older and younger siblings help children learn to manage emotions, develop empathy, and improve their social skills. The conclusion of this study shows that sibling relationships play an important role as a source of emotional support within the family and contribute positively to children's emotional development.